PENGARUH MEDIA PEMBELAJARAN MENGGUNAKAN APLIKASI PIJAR SEKOLAH TERHADAP PEMBELAJARAN PADA MATA PELAJARAN SOSIOLOGI SMA AL-ISTIQAMAH KABUPATEN PASAMAN BARAT - Riyanti, Fajri Putri; Yasin, Faishal; Wahyuni, Yanti Sri (Jurnal Manajemen Pendidikan, 2025)
Learning is an active interaction process between individuals and their environment that can lead to positive behavioral changes. This study aims to empirically examine the effect of using the Pijar Sekolah application as a learning medium on the effectiveness of Sociology learning at Al-Istiqamah Senior High School, West Pasaman Regency. A quantitative approach was employed using a survey method. Primary data were collected through questionnaires, while secondary data were obtained from school documents. A purposive sampling technique was used to select 40 students from grade X, phases E1 to E8. Data analysis was conducted using simple linear regression with the assistance of SPSS version 25, preceded by descriptive analysis, classical assumption tests, and hypothesis testing (t-test and F-test). The results showed that the use of the Pijar Sekolah application had a significant effect on student learning outcomes, with a significance value of 0.000 (p < 0.05) and a t-value of 3.082, indicating that the alternative hypothesis is accepted. The novelty of this research lies in the application of Pijar Sekolah as a digital learning medium in Sociology subjects at the senior high school level, which remains underexplored in previous empirical studies, particularly in the West Pasaman region.